Tekst religijny w politycznym przetworzeniu – „Gorzkie żale moskalofilskie” Telesfora Chełchowskiego - Klimek-Grądzka, Jolanta (Stylistyka, 2020)
Telesfor Chełchowski’s Gorzkie żale moskalofilskie [The Moscophile Lenten Lamentations] (1917) is a text which corresponds to the poetics of political disputes of the Polish in exile at the turn of the 19th and the 20th century. At the same time, the author draws on from the Polish literary tradition. Through making references to the prayer convention and model – Lenten (Bitter) Lamentations – and taking into account the genesis, Chełchowski’s text can be regarded as travesty or a specimen of the model. This reference manifests itself in the structure: 1) Awakening; 2) Considerations; 3) three identically complex parts which are internally structured, that is Hymn boleści [A hymn of anguish], Lament moskafilów nad cierpiącym ekscarem [A lament of Moscophiles over the suffering ex-Tsar], Wesoła rozmowa moskofila z koniowcem [A merry talk between a Moscophile and a horsephile]; 4) Zakończenie lamentów moskafilskich [The conclusion of Moscophile laments], as well as in the consistently applied metric model, stylistic and semantic references.